Evaluation of Anxiety and Depression Levels in High-Risk Pregnancies During the COVID-19 Pandemic and Their Approaches to Vaccination: A Case-Control Study - Seval Yilmaz Ergani; Huriye Guvenc Sacinti; Mujde Can Ibanoglu; Kadriye Yakut Yucel; Caner Kose; Nazan Vanli Tonyali; Elif Gulsah Diktas; Rahmi Sinan Karadeniz; Can Tekin Iskender; Yaprak Ustun (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Anxiety and depression are associated with the interaction of many social factors, but pregnancy and puerperium are periods when patients are particularly sensitive to depression and anxiety. Assessing the level of anxiety and depression in high-risk pregnancies during the pandemic process and their attitudes toward vaccination.